Dune. Part two [videorecording (Blu-Ray)] - Villeneuve, Denis, 1967-; Spaihts, Jon, 1970-; Chalamet, Timothée; Zendaya, 1996-; Ferguson, Rebecca, 1983-; Brolin, Josh; Butler, Austin, 1991-; Pugh, Florence, 1996-; Bautista, David, 1969-; Walken, Christopher, 1943-; Seydoux, Léa, 1985-; Skarsgård, Stellan; et al. (Warner Bros. Entertainment Inc., 2024)
"...[T]he mythic journey of Paul Atreides as he unites with Chani and the Fremen while on a warpath of revenge against the conspirators who destroyed his family. Facing a choice between the love of his life and the fate of the known universe, he endeavors to prevent a terrible future only he can foresee" --Container.